Características agronômicas e índices de trocas gasosas do tomateiro em função de sistemas de condução em ambiente protegido - Hachmann, Tiago Luan (2015)
This work was conducted in the period from April, 11th, 2014 until September, 9th, 2014 aiming studying the influence of the number of stems and the way of establishing these stems in productivity and quality characteristics of the tomato cultivars, and evaluate the daily course of gas exchange indexes of the tomato cultivars in the leaves exposed to solar radiation from the east (morning) or the west (afternoon). The experimental design used in the first experiment was a randomized block design with factorial 3 x 2 x 2, with four replications. Three numbers of stem per plant were tested (one, two and four steams) two forms of establishment (maintaining and removing the main stem) and two cultivars (Caniles and Rubi F1 hybrid). The total number of fruits, number of normal fruits, non-commercial and blossom-end rot was evaluated; percentage of unmarketable fruits and blossom end rot; average mass, longitudinal and transversal diameter of the normal fruits; fruit mass, transversal and longitudinal diameter, average fruit mass and productivity of the first four clusters; total mass of fruit and fruit normal mass; and was calculated productivity of normal fruits, non-commercial, with blossom end rot and total fruit yield. It was also evaluated pH, soluble solids, titratable acidity and soluble solids/titratable acidity ("ratio"). In the second experiment the experimental design was a randomized block design, factorial 2 x 2 x 6, with four replications. The first factor was composed of two evaluation positions in the plant (East and West), the second of two tomato cultivars (Caniles and Rubi) and finally six times evaluation throughout the day (8:00, 10:00, 12:00, 14:00, 16:00 and 18:00). It was measured the rate of CO2 net assimilation (A), leaf transpiration (E), stomatal conductance (gs), internal CO2 concentration (Ci) and leaf temperature (°C) and vapor pressure deficit. It was also calculated the water use efficiency (WUE) (A/E), intrinsic water use efficiency (WUEi) (A/gs) and the instantaneous efficiency of carboxylation (A/Ci). The conduction of plants with four steams is more favorable to productivity and the quality characteristics. The establishment of steams number keeping the main stem is best suited for providing greater productivity. The cultivar Caniles is the most suitable for driving on growing conditions, due to its higher yield and fruits with better "ratio". The values of net assimilation rate of CO2, leaf transpiration, stomatal conductance, leaf temperature, water use efficiency, intrinsic water use efficiency and instantaneous carboxylation efficiency on the east side are larger than on the west side. The cultivar Caniles has a higher net assimilation rate of CO2, leaf transpiration, leaf temperature and instantaneous carboxylation efficiency under conditions of high temperature and luminosity